Factors associated with the dropout between BCG and measles immunization in Krishnanagar illaka of Kapilvastu- district. - Gautam, Kamal (2007)
SUMMARY: A study on factors associated with dropout between BCG and Measles Immunization in Krishnanagar Illaka of Kapilvastu District" was carried out in Krishnanagar Illaka of kapilvastu. The study attempted to explore the situation of enhancing factors for drop-out. The main objective of the study was to find out the reasons responsible for drop-out between BCG and measles immunization on Krishnanagar Illaka. A purposive cross-sectional comparative study design was used for this purpose. The study population were the children of 12-23 months residing in 4 VDCs name krishnanagar, Ramnagar Bhagawanpur andShirshihawa. The VDCs were chosen with registers of chosen VDCs. Same number of children i.e. 50 children from similar socio-economic status family residing in same place were also taken to compare with sampled children. Key informant interview were performed with village health worker, maternal child jealth worker, Health-institution incharges and focus group discussion was performed with FCHVs. The study revealed that Muslim ethnic group was found highly dropping out (44%) followed by disadvantaged non-dalit terai caste group (30%) and upper cast group (18%). The immunization card retention was 38% among defaulted and 40% among fully immunized group. However the card keeping was not safe. The higher proportion of population was of children of birth order 2-5 for both groups of children. Nearly 72% of mothers of defaulted children were illiterate followed by literate (2250 . Likewise 52% mothers of fully immunized children were illiterate and only 4% were of secondary education. Regarding father's education, majority of fathers of defaulted children were literate (34%) followed by literate (325). Similarly 26% fathers of fully immunized children were primary educated followed by illiterate and lower secondary education 22% each. Majority of both group of respondents were found to immunize their children with BCG antigen, on the basis of information provided by FCHV followed by information given by relatives. The main causes of default of measles vaccination found was absence of mother for a long time throughout the time of vaccination (28%) followed by lack of knowledge, fear of side effects and child being sick at the time of immunization 16% each. Death of mother had also significant role for drop out. Among fully immunized ones the main factor responsible for completion of vaccination was timely information given by FCHV (56%0 followed by well counseling and timely information of services provider (22%). Information was also provided by service provider in other places which had significant role for completion of immunization schedule. More than half of the respondents of defaulted children and 62% respondents of fully immunized children said vaccination was for protection from disease. However they could not say specific diseases protected by specific antigen. None of the respondents of defaulted children could reply correctly regarding type of antigens to vaccinate, time of each antigen to be vaccinated and proper age of children to vaccinate for each dose. Only 10% respondents of fully immunized children group could explain correctly about types of antigen to vaccinate and time of each antigen to be vaccinated and only 8% could explain proper age of children to immunize for each dose. Information regarding time and site of EPI clinic was given by FCHVs most of the time, Overall performance of FCHVs was found good. They reminded the families for children to be immunized in time and supported in immunization clinic. People who have better relation with FCHVs were found more likely to complete vaccination. The overall performance of service provides was found satisfactory I terms of behaviour, relation with community people and counseling aspect. Interview with health facility incharges and service providers revealed that the major cause of drop out was lack of awareness and absence of mother throughout the time of vaccination. EPI clinics were running regularly but adequate supervision and monitoring are lacking.